A ligation assay for multiplex analysis of CpG methylation using bisulfite-treated DNA - Dahl, Christina (Oxford University Press, 2007)
Aberrant methylation of promoter CpG islands is causally linked with a number of inherited syndromes and most sporadic cancers, and may provide valuable diagnostic and prognostic biomarkers. In this report, we describe an approach to simultaneous analysis of multiple CpG islands, where methylation-specific oligonucleotide probes are joined by ligation and subsequently amplified by polymerase chain reaction (PCR) when hybridized in juxtaposition on bisulfite-treated DNA. Specificity of the ligation reaction is achieved by (i) using probes containing CpGpCpG (for methylated sequences) or CpApCpA (for unmethylated sequences) at the 3′ ends, (ii) including three or more probes for each target, and (iii) using a thermostable DNA ligase. The external probes carry universal tails to allow amplification of multiple ligation products using a common primer pair. As proof-of-principle applications, we established duplex assays to examine the FMR1 promoter in individuals with fragile-X syndrome and the SNRPN promoter in individuals with Prader-Willi syndrome or Angelman syndrome, and a multiplex assay to simultaneously detect hypermethylation of seven genes (ID4, APC, RASSF1A, CDH1, ESR1, HIN1 and TWIST1) in breast cancer cell lines and tissues. These data show that ligation of oligonucleotide probes hybridized to bisulfite-treated DNA is a simple and cost-effective approach to analysis of CpG methylation.